In-silico study of Stevia Leaves (Stevia rebaudiana Bertoni) as Antidiabetic Drugs - Mustarichie, Resmi; Junaedi, Effan (Asian Journal of Pharmaceutical Research and Development, 2021)
Diabetes mellitus is a metabolic disorder due to abnormalities in insulin secretion, insulin action or both. Around 200 million people worldwide suffer from diabetes, most of which is type 2 diabetes. One of the targets of diabetes treatment is the DPP-4 enzyme which works to degrade incretin from the body. Sitagliptin, a DPP-4 inhibitor that has been approved for the treatment of type 2 diabetes. Besides using cytetic drugs, biochemical compound can also be used for diabetes therapy, one of which is stevia leaf. This research was conducted to select compounds contained in stevia leaves based on their interaction with DPP4 in silico. The purpose of this study is a potential compound from stevia leaves to be a candidate for antidiabetic drugs. Tests were carried out on DPP4 inhibitors, namely sitaglipin, and 10 compounds contained in stevia leaves. The results show that there are three potential compounds namely isosteviol, steviol and steviolmonoside. Testing the Lipinski’s rule of five and pre-ADMET parameters shows that the three compounds have the potential to be used as candidates for antidiabetic drugs.